THE IMPORTANCE OF COMPUTER TECHNOLOGY IN TEACHING BIOLOGY - Rustamov Abubakrsiddiq Muhammadjon ugli (Web of Journals Publishing, 2024)
This article provides information on improving students knowledge through the use of information technologies in teaching biology, and the advantages of using computer technologies in biology classes.
Keywords: biology, teaching methodology, computer technologies, information, education.